STUDY TENTANG KEMANDIRIAN PESERTA PASCA PELATIHAN RIAS PENGANTIN DI BLK KOTA PADANG - Silga Matha Wahyuni; Linda Rosalina (Jurnal Tata Rias dan Kecantikan, 2021)
This study examines the independence of participans after bridal makeup at BLK Padang City. The development of life today requires everyone to try to improve the quality of the next life that is better,be it in terms of informal or non-formal. This study aims to determine how the independence of post paricipants and the inhibiting factors in bridal makeup training at BLK Padang city. The method used in this research is descriptive qualitative with an observation opproach. The purpose of using descriptive qualitative methods is because the problems studied are not related to numbers but rather describe the independence of participants after bridal makeup training at the BLK work training center in Padang city. In this study, the data collection techniques used were observation, interview, and documentation techniques. Observation technique is a technique in data collection to obtain data through direct observation in the field regarding the independence study of participants after bridal makeup training at BLK Padang City.The mumber of participants after the bridal makeup training at the padang city BLK was 21 people, while the sample used was 10 people. The results of this study indicate that there are several things about the independence of the participants after the bridal makeup training,as well as the independence faktor of the participants after the bridal makeup training at the padang city BLK.